2020
DOI: 10.3390/nu12020583
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Roles of Vitamin K in Progression of Vascular Calcification

Abstract: Vitamin K is a fat-soluble vitamin that is indispensable for the activation of vitamin K-dependent proteins (VKDPs) and may be implicated in cardiovascular disease (CVD). Vascular calcification is intimately associated with CV events and mortality and is a chronic inflammatory process in which activated macrophages promote osteoblastic differentiation of vascular smooth muscle cells (VSMCs) through the production of proinflammatory cytokines such as IL-1β, IL-6, TNF-α, and oncostatin M (OSM) in both intimal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 116 publications
(137 reference statements)
0
60
0
3
Order By: Relevance
“…Ample evidence has shown that VK deficiency is related to the pathogenesis of VC [81][82][83][84]. VK has been suggested to inhibit VC and protect against cardiovascular disease (CVD) through the activation of VKDPs, such as MGP.…”
Section: Vitamin K In the Prevention And Therapy Of Vascular Calcification And Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ample evidence has shown that VK deficiency is related to the pathogenesis of VC [81][82][83][84]. VK has been suggested to inhibit VC and protect against cardiovascular disease (CVD) through the activation of VKDPs, such as MGP.…”
Section: Vitamin K In the Prevention And Therapy Of Vascular Calcification And Cardiovascular Diseasesmentioning
confidence: 99%
“…VC, a hallmark of senescence and a strong predictor of CV events, is another chronic inflammatory state induced via the generation of proinflammatory cytokines and mediated by the NF-кB signaling pathway. A high VK status may exert anti-inflammatory effects and prevent VC through antagonizing NF-кB signaling [83]. Growing evidence shows that VK as well as nuclear factor erythroid 2-related factor 2 (Nrf2) signaling could play a vital role in blocking ROS generation, cellular senescence, DNA damage, and inflammaging [84].…”
Section: Vitamin K In the Prevention And Therapy Of Vascular Calcification And Cardiovascular Diseasesmentioning
confidence: 99%
“…The most well-known VKDP produced by smooth muscle cells is MGP that inhibits vascular calcification. A higher circulatory level of dp-ucMPG, the best vitamin K insufficiency marker, has been related to a higher risk of vascular calcification, cardiovascular events, and CVD mortality [ 10 , 23 ]. The anti-inflammatory effects of vitamin K also increase the possibility of its contribution to cardiovascular health [ 10 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher circulatory level of dp-ucMPG, the best vitamin K insufficiency marker, has been related to a higher risk of vascular calcification, cardiovascular events, and CVD mortality [ 10 , 23 ]. The anti-inflammatory effects of vitamin K also increase the possibility of its contribution to cardiovascular health [ 10 , 22 ]. Higher intakes of dietary vitamin K have been associated with the lower risk of total coronary heart disease based on the pooled data from prospective studies on associations between dietary intakes of vitamin K1 ( n = 4) and K2 ( n = 2) and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation